Adaptive ecology of the King’s skink, Egernia kingii, in response to varying levels of predation risk, with a focus on caudal autotomy - Barr, James Ian (Curtin University, 2020)
Anti-predation strategies allow individuals to avoid death but can be costly to the individual. As predation pressure changes ontogenetically, temporally and evolutionarily, so do costly anti-predation strategies to minimise maximise survival but minimise associated costs. I investigate how caudal autotomy changes morphologically and behaviourally within a large scincid the King’s skink (Egernia kingii) both ontogenetically and across predation gradients.